Effect of Brazilian green propolis in chronic ulcer treatment: a randomized clinical trial - Pascalle de Sousa Rocha; Luis Rafael Leite Sampaio; Gyllyandeson de Araújo Delmondes; Andreza Gysllaynny Delmondes Saraiva; Fábio Ferreira Perazzo; Fernando Luiz Affonso Fonseca; José Lucas de Souza; Luis Fernando Reis Macedo (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objective: to assess the effectiveness of 5% Brazilian green propolis (ointment) in individuals with chronic ulcers. Methods: a randomized clinical trial, developed with 40 patients randomized equally to control group (treated with essential fatty acid) and experimental group (treated with 5% green propolis) for 30 days. The outcomes of interest were sociodemographic, clinical and laboratory characteristics, lesion characteristics, such as type of tissue in the bed, presence of exudate, edge characteristics, microbial content and pain. Results: regarding sociodemographic, clinical and laboratory characteristics, the two groups did not show statistically significant differences. After assessment in 30 days, an effect was observed for both treated groups, but for the experimental group, greater effectiveness in terms of the type of tissue in the bed, type of exudate, edge characteristics, microbial content and pain. Conclusion: propolis-based ointment showed a healing effect, presenting itself as a potential tool in healing chronic ulcers.